Athletic Pubalgia – A Significant Diagnostic and Therapeutic Challenge in Athletes? - Ząbek, Adam Jan; Kuźniar, Jakub Paweł; Chrzanowska, Emilia Gabriela; Zagalska, Michalina; Turek, Marta; Tamborski, Tomasz; Grzebinoga , Adam; Szlążek, Julia; Roguska, Barbara; Mitręga, Karolina Maria (Journal of Education, Health and Sport, 2025)
Introduction: Athletic pubalgia is a clinical syndrome involving overuse injuries of the musculo-tendinous structures around the pubic symphysis. It primarily affects athletes engaged in sports requiring rapid directional changes, kicking, and high core and lower limb load. This study aims to present the current understanding of the pathophysiology, epidemiology, clinical presentation, and treatment strategies of athletic pubalgia. Methods: A review of 25 scientific publications from PubMed and Google Scholar was conducted. The analysis focused on risk factors, clinical symptoms, diagnostic approaches, and both conservative and surgical management strategies in athletes. Results: Athletic pubalgia predominantly affects male athletes in soccer, hockey, and American football. Symptoms include exertional groin pain. Diagnosis is based on clinical assessment, functional testing, and imaging—especially MRI. Conservative treatment involving physiotherapy and postural re-education is effective in most cases. Refractory cases may require surgical intervention such as posterior inguinal wall repair or adductor tenotomy. Conclusions: Athletic pubalgia presents a significant diagnostic and therapeutic challenge. Effective management requires an interdisciplinary and individualized approach. Further clinical studies are needed to develop standardized diagnostic and therapeutic algorithms.